Relationship between Tactical Behavior and Affective Decision-Making in U-17 Youth Soccer Players - Santos Rodrigo (Human Movement, 2014)
Purpose. The aim of this article was to analyze the relationship between tactical behavior and affective decision making of U-17 youth soccer players. Methods. The sample was comprised of 154 participants meeting the study inclusion criteria. Players played 4-min games on four-person teams (including goalkeeper) on a small-sided soccer field. The System of Tactical Assessment in Soccer (FUT-SAT) was used to determine the defensive tactical actions performed by players according to five different tactical principles. A total of 6140 defensive tactical actions were recorded. Their affective decision-making was measured by a computerized card task, the Iowa Gambling Task (IGT). Results. Significant negative correlation was found between players’ learning curve and the incidence of actions based on the principle of concentration. Less impulsive players presented a lower incidence of actions tied with the principle of concentration in comparison with more impulsive players. Conclusions. The findings suggest that, in the defensive phase, players who are less impulsive decision makers may benefit from more secure and stable defensive styles.